1989
DOI: 10.1002/mana.19891410108
|View full text |Cite
|
Sign up to set email alerts
|

On the Reflectiveness and Coreflectiveness of Subcategories of FTS

Abstract: PreliminariesWe assume familiarity with most of the usual notational conventions in the field and limit ourselves to recalling only the most important concepts and definitions required in this paper.Our basic category is FTS which stands for the topological category [l] of fuzzy topological spaces and continous maps as introduced in [3]. MAX stands for the full isomorphism closed subcategory of l?TS which was essentially introduced in [9]. In order to reformulate its definition we recall the notion of level to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…It was shown that MAX [10] is a bicoreflective subcategory of SI-TOP but it is not a reflective subcategory of SI-TOP, that is, MAX is not stable.…”
Section: (4) Stab( ) Is Coreflective and The Coreflection Of (I ) Ismentioning
confidence: 98%
See 1 more Smart Citation
“…It was shown that MAX [10] is a bicoreflective subcategory of SI-TOP but it is not a reflective subcategory of SI-TOP, that is, MAX is not stable.…”
Section: (4) Stab( ) Is Coreflective and The Coreflection Of (I ) Ismentioning
confidence: 98%
“…We write c ( ) for ( ( )) c , the set of closed subsets of (X, ( )). In [14] the full subcategory MAX of SI-TOP was essentially introduced, then its reformulation, in [10], was defined in the following way: the relation between objects (X, ) and (X, ) of SI-TOP, defined by…”
Section: (4) Stab( ) Is Coreflective and The Coreflection Of (I ) Ismentioning
confidence: 99%
“…(A fuzzy topological space is called weakly induced if all u E 7" are lower semicontinuous when considered as mappings u : (X, ~-N 2 x) -> I, [135].) The category w(Top) of all topologically generated spaces is coreflexive in LeFT(I), the coreflexiones given by Lw: (X,T) ---> (X,~wT) [126].…”
Section: X T X) -+ ( Y T Y) the Mapping W(f) = F: ( X Wt X) --+ ( mentioning
confidence: 99%
“…One of their nice aspects is that they can also be characterized as topological categories in which coproducts and quotients are preserved under pullbacks along projections. UNIF) as bicorefiective subcategories closed under the formation of finite products [Wuyts, Lowen and Lowen 1988;Lowen, Wuyts and Lowen 1989]. The categories FTS and FNS (resp.…”
Section: E Lowen R Lowen §O Introductionmentioning
confidence: 99%